Morphological and physiological response of two populations of Quercus ilex L. to SO2 fumigation - Infante, J M; Garcia-Laureano, R; Merino, J (PHYTON-ANNALES REI BOTANICAE, 2002)
Quercus ilex L., is the predominant evergreen schlerophyllous tree in the Mediterranean landscape of the Iberian Peninsula. Fruit acorns were collected in two populations located in the center (southern Spain) and at the northern border (northern Spain; a distance of 800 km) of the distribution area of Quercus ilex. One-month-old potted plants were grown for 130 days to a high SO2 concentration (0.23 ppm, 14 h d(-1)) under controlled climate conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
Keywords: air pollution; Mediterranean ecosystems; Populations; Quercus ilex; Sulfur Dioxide

Modelling leaf gas exchange in holm-oak trees in southern Spain - Infante, J M; Damesin, C (Agricultural and Forest …, 1999)
This paper presents a mechanistically based C3 leaf CO2 assimilation model linked with an empirical stomatal model to simulate Quercus ilex leaf net photosynthesis and transpiration in oak-savannah ecosystems of southern Spain. The model estimates (time integration) daily and seasonal changes in carbon ®xation, transpiration, and water use ef®ciency of a single leaf in free air. Simulations were carried out on two trees for a dry year. Results shown in our study demonstrate that the modelling approach, compared to ®eld measurements, provides a realistic description of diurnal and seasonal patterns of leaf gas-exchange response to different environmental conditions, and as affected by water availability
Keywords: carbon dioxide assimilation; Drought; leaf gas exchange; oak savannah; photosynthesis model; Quercus ilex

Modelling transpiration in holm-oak savannah: scaling up from the leaf to the tree scale - Infante, J M; Rambal, S; Joffre, R (Agricultural and Forest Meteorology, 1997)
The transpiration of oak-savannas in southern Spain was modelled by scaling-up from the leaf to the tree during a drought period. Two chlaracteristics of this ecosystem were found to facilitate the modelling procedure. The first was a near-zero decoupling coefficient between the surface and the surrounding bulk air, which simplifies the transpiration formulation. The second was that the surface conductance (g) is mainly related to the vapour pressure deficit of the air (0,). Based on both of these characteristics, the modelling procedure provides a general model of transpiration over the time scale appropriate for a drought period, from days to months. The response of g to 0, was found to follow a negative exponential function, such that beyo’nd a minimum value, g becomes independent of 0,. This implies a feedback control on g by 0,. The consequences of tbis control for transpiration were found at different levels of plant water status. This explains the plants’ adaptation to long dry periods, even though there is also continuous water loss during these periods. Such an adaptation was corroborated by a seasonal hysteresis found in the relationship between transpiration and D, as a function of the plants’ water status
Keywords: oak savannas; seasonal hysteresis; southern Spain; Transpiration; vapour pressure deficit